2021
DOI: 10.1002/ajim.23233
|View full text |Cite
|
Sign up to set email alerts
|

Initial return to work and long‐term employment patterns: Associations with work‐related permanent impairment and with participation in workers' compensation‐based return‐to‐work programs

Abstract: Background Roughly 10% of injured workers experience work injuries that result in permanent impairment and a permanent partial disability (PPD) award. This study aimed to characterize and quantify long‐term employment outcomes for injured workers, by the degree of whole body impairment (WBI) and by participation in several workers' compensation (WC)‐based return‐to‐work (RTW) programs. Methods A retrospective cohort of 43,968 Washington State workers were followed for up to 10 years after WC claim closure (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 48 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…The focus on safety‐related issues comports with previously published data from the same survey, which revealed that more than half of respondents thought their permanent impairment put them at higher risk of being reinjured at work, compared with pre‐injury (65.2%), or compared with coworkers in the same job (54.4%) 22 . The focus on safety‐related issues also aligns with findings from a large retrospective cohort of injured workers with WC claims linked to wage data, in which workers with work‐related permanent impairments had significantly higher reinjury risk compared with workers without permanent impairments—a risk differential that increased as degree of permanent impairment increased 11 …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…The focus on safety‐related issues comports with previously published data from the same survey, which revealed that more than half of respondents thought their permanent impairment put them at higher risk of being reinjured at work, compared with pre‐injury (65.2%), or compared with coworkers in the same job (54.4%) 22 . The focus on safety‐related issues also aligns with findings from a large retrospective cohort of injured workers with WC claims linked to wage data, in which workers with work‐related permanent impairments had significantly higher reinjury risk compared with workers without permanent impairments—a risk differential that increased as degree of permanent impairment increased 11 …”
Section: Discussionmentioning
confidence: 58%
“…The open‐ended questions we included, in addition to corroborating the importance of the workplace factors covered by pre‐specified survey questions, also enabled the presentation of workers' voices with respect to the workplace factors they considered most important to their wellbeing. Another strength was that the survey was focused on the first year after claim closure—a time period which is high‐risk for reinjury and job loss, and which may also determine long‐term employment prospects 11,18 . However, because we interviewed only workers who had RTW at least briefly, our findings do not directly address workplace improvements that might facilitate RTW for workers with permanent impairments who do not RTW at all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite having been deemed able to work, many workers with PPD awards do not RTW. 4,5 Those that do RTW face elevated risks of delayed RTW, RTW interruption, and reinjury (relative to workers without PPD awards), 5,6 which may be related to factors such as long-term functional disability, pain, unstable health, layoff, early retirement, negative treatment by managers and coworkers, lack of accommodation, and discrimination. 4,[6][7][8][9][10][11][12] Some of the multiple factors predisposing workers to negative outcomes-particularly workers with permanent impairments-may be amenable to intervention via WC-based vocational rehabilitation and other RTW programs, and overall WC system improvements.…”
Section: Introductionmentioning
confidence: 99%